Stop that bull, Theseus! : Myth-O-Mania #5 - McMullan, Kate; Zilber, Denis (Mankato, Minn. : Stone Arch Books, 2012)
In this modern version of Greek mythology, Hades, King of the Underworld, tells the true story of Theseus finding his way through the labyrinth to slay the Minotaur.
Keywords: Hades (Greek deity) -- Juvenile fiction; Theseus (Greek mythology) -- Juvenile fiction; Minotaur (Greek mythology) -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Hades (Greek deity) -- Fiction; Theseus (Greek mythology) -- Fiction; Minotaur (Greek mythology) -- Fiction; Mythology, Greek -- Fiction; Hades (Greek deity) -- Fiction; Theseus (Greek mythology) -- Fiction; Minotaur (Greek mythology) -- Fiction; Greek mythology -- Fiction; Humorous fiction; Humorous fiction